2023
DOI: 10.1136/gutjnl-2022-329304
|View full text |Cite
|
Sign up to set email alerts
|

Australian inflammatory bowel disease consensus statements for preconception, pregnancy and breast feeding

Abstract: ObjectiveBecause pregnancy outcomes tend to be worse in women with inflammatory bowel disease (IBD) than in those without, we aimed to update consensus statements that guide the clinical management of pregnancy in patients with IBD.DesignA multidisciplinary working group was established to formulate these consensus statements. A modified RAND/UCLA appropriateness method was used, consisting of a literature review, online voting, discussion meeting and a second round of voting. The overall agreement among the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 226 publications
0
9
0
Order By: Relevance
“…Tofacitinib level in breast milk was found to exceed maternal serum levels 15 . Tofacitinib should be avoided in breastfeeding 4 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tofacitinib level in breast milk was found to exceed maternal serum levels 15 . Tofacitinib should be avoided in breastfeeding 4 …”
Section: Discussionmentioning
confidence: 99%
“…11,12 Tofacitinib use for IBD in pregnancy is not recommended, and cessation for 4-8 weeks is advised before conception; this is based on its foeticidal and teratogenic potential in animal studies and due to the lack of evidence of use in humans. 4,13 It is assumed that tofacitinib can cross the placenta due to its small molecular size, although this has yet to be formally tested and studied. Animal studies showed increased loss of pregnancy and lower mean foetal body weight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations